Coronary artery bypass for angina pectoris. Issue 14 (6th July 1973) - Unknown
Abstract : Many attempts have been made to increase the blood flow to ischaemic myocardium by surgical means but most have been unsuccessful. Recently however a technique has been developed 1 which may be an advance. The procedure, which involves placing a vascular bypass across the arterial block, has been pioneered in North America where it is used routinely as a treatment for severe angina. It is now also being carried out in an increasing number of hospitals in the United Kingdom.